PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Ni Wayan Pari Santi; I Made Sujana Adnyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low mathematics learning outcomes of third-grade elementary school students due to limited student engagement in the learning process. This study aimed to improve mathematics learning outcomes through the implementation of the discovery learning model. This research used classroom action research conducted in two cycles, including planning, action, observation, and reflection stages. The subjects were third-grade elementary school students. Data were collected through tests and observations. The results show that the implementation of the discovery learning model improves students’ mathematics learning outcomes gradually in each cycle. In addition, students’ participation in learning also increases. Therefore, it is concluded that the discovery learning model is effective in improving mathematics learning outcomes of elementary school students.